The Role of Bitter Watermelon (Abujahl Watermelon) in Human Health and Folk Medicine (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the effects of bitter watermelon (Abujahl watermelon) on human health, its medicinal properties, and its use and significance in folk medicine. It was found that most of the patients who consumed bitter watermelon juice for 2-3 days had a blood glucose level close to normal.